1965
DOI: 10.1037/h0022383
|View full text |Cite
|
Sign up to set email alerts
|

Ego involvement and the absolute judgment of attitude statements.

Abstract: Personal involvement in a social issue was manipulated both experimentally and by S selection while controlling for extremity of attitude. The effects on the absolute judgment of relevant attitude statements then was observed. The more highly involved was S, the further from his own position the statements were judged. This effect was not significant for statements on 2 irrelevant attitude scales. The Involvement X Item Position interaction was not significant. These results were interpreted as providing suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

1969
1969
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
16
2
Order By: Relevance
“…Although the questionnaire included no direct measure of subjects' involvement, an indirect test of this possibility may be made by inspection of subjects' overall mean ratings on each scale (Table s). While Sherif and his co-workers do not regularly draw a sharp distinction between involvement and extremity of own position, those studies which have attempted to do so (Ward, 1965(Ward, , 1966 imply that greater involvement should lead to a more marked inverse relationship between mean rating and own position, which should mean that the effects of attitude and high v. low polarizers should significantly interact in the analysisof subjects' mean ratings, which they do not, It would thus seem unlikely that the differences between high and low polarizers could be attributed to differential levels of involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Although the questionnaire included no direct measure of subjects' involvement, an indirect test of this possibility may be made by inspection of subjects' overall mean ratings on each scale (Table s). While Sherif and his co-workers do not regularly draw a sharp distinction between involvement and extremity of own position, those studies which have attempted to do so (Ward, 1965(Ward, , 1966 imply that greater involvement should lead to a more marked inverse relationship between mean rating and own position, which should mean that the effects of attitude and high v. low polarizers should significantly interact in the analysisof subjects' mean ratings, which they do not, It would thus seem unlikely that the differences between high and low polarizers could be attributed to differential levels of involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent researchers have offered cognitive accounts for why contrast effects should be greater for egoinvolved individuals. For example, Ward (1965) suggested that the attitudes of ego-involved individuals may be more cognitively salient. Similarly, accentuation theorists have suggested that personal involvement might make a peripheral agree-disagree evaluation more salient, thus prompting greater contrast effects (Eiser & van der Pligt, 1984;Judd & Harackiewicz, 1980).…”
Section: A Motivational Perspective On Contrast Effectsmentioning
confidence: 99%
“…Several studies have measured categorization complexity across more than one domain of stimuli for the same Ss (Glixman, 1965;Ward, 1965;Larsen, 1971). In these studies, the Ss were presented with several different domains of sentences, preselected to vary in involvement.…”
Section: Arizona State University Tempe Arizona 85281mentioning
confidence: 99%